Fabricating and determining representative volume elements of two-dimensional random aggregate numerical model for asphalt concrete without damage. (28th November 2022) - Liang, Sheng; Liao, Menghui; Tu, Chongzhi; Luo, Rong
Highlights: An RVE fabricating method for 2D random aggregate numerical model of asphalt concrete was proposed, which can be used to fabricate RVEs of various sizes. 9 different sizes of RVEs corresponding to AC-13C, AC-20C and AC-25C asphalt concrete were fabricated. Geometric analysis and virtual dynamic modulus tests were performed for RVEs. The minimum sizes of RVE for AC-13C, AC-20C and AC-25C asphalt concrete in the nondestructive state were determined. Abstract: In order to optimize the fabricating method of representative volume element (RVE) for two-dimensional (2D) random aggregate numerical model of asphalt concrete, and determine the minimum size of RVE corresponding to the 2D random aggregate numerical model of typical graded asphalt concrete in the nondestructive state. The authors first proposed an RVE fabricating method that includes "aggregate region identification" algorithm and can place "partial aggregate". Then, by using this method, 9 different sizes of RVEs corresponding to AC-13C, AC-20C and AC-25C asphalt concrete (AC-13C, AC-20C and AC-25C asphalt concrete are dense-graded asphalt mixtures, and their nominal maximum aggregate sizes are 13.2 mm, 19 mm and 26.5 mm respectively) were fabricated. Subsequently, the geometric characteristics (aggregate area proportion, aggregate angle, "density" homogeneity) of these RVEs were analyzed. After that, virtual dynamic modulus tests were performed on these RVEs. Finally, the results of geometric analysis and virtual dynamic modulus test were comprehensively analyzed. The results show that the "aggregate region identification" algorithm can effectively improve the aggregate placement efficiency. By placing "partial aggregate", the RVEs with small-sizes that meet the requirements of aggregate area proportion in each particle size range can be fabricated. In the nondestructive state, the minimum sizes of 2D random aggregate numerical model's RVE corresponding to AC-13C, AC-20C and AC-25C asphalt concrete are 20 mm, 30 mm and 40 mm respectively.